2018
DOI: 10.1111/josi.12297
|View full text |Cite
|
Sign up to set email alerts
|

Immigration and Receiving Communities: The Utility of Threats and Emotions in Predicting Action Tendencies toward Refugees, Asylum‐Seekers and Economic Migrants

Abstract: Traditional accounts of intergroup bias often fail to consider the complexity of intergroup phenomena by insufficiently distinguishing between (a) attitudes, emotions and action tendencies, (b) classes of threat that promote intergroup bias and (c) subtle category distinctions amongst social groups. We develop a nuanced account of antimigrant bias by distinguishing between (a) manifestations of bias in emotions and action tendencies, (b) kinds of threat that drive antimigrant bias, and(c) kinds of migrant grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
2
21
0
1
Order By: Relevance
“…These results suggest that inclusive identities are positively related with attitudes toward the immigration target directly involved in the representation, but such positive relation may not generalize to more distal immigration targets, like North African immigrants or immigrants in general. While unexpected, these dissociations between immigration attitude indicators have some resemblance to documented differences in sensitivity between affective and cognitive indicators of outgroup attitudes reported in the literature (Abeywickrama, Laham, & Crone, ; Paolini, Hewstone, & Cairns, ; Tropp & Pettigrew, ). Also, in a similar vein, Dixon, Durrheim, and Tredoux () found dissociations between personally held attitudes toward ethnic equality and responses to related policy issues.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These results suggest that inclusive identities are positively related with attitudes toward the immigration target directly involved in the representation, but such positive relation may not generalize to more distal immigration targets, like North African immigrants or immigrants in general. While unexpected, these dissociations between immigration attitude indicators have some resemblance to documented differences in sensitivity between affective and cognitive indicators of outgroup attitudes reported in the literature (Abeywickrama, Laham, & Crone, ; Paolini, Hewstone, & Cairns, ; Tropp & Pettigrew, ). Also, in a similar vein, Dixon, Durrheim, and Tredoux () found dissociations between personally held attitudes toward ethnic equality and responses to related policy issues.…”
Section: Discussionsupporting
confidence: 71%
“…Future research could further examine the potential differential impact of different conceptualizations of national identity on attitudes toward immigrants and immigration policies that are framed in both positive and negative ways, white carefully controlling for weight of affect, cognitions, and behavior. Additionally, future studies could also consider the specific type of migrant (e.g., economic migrant, refugee, asylum seeker) as research shows differences on threat appraisals, emotions and behavioral intentions when those different labels are activated (e.g., Abeywickrama et al., ; Hartley & Pedersen, ). This could be particularly relevant to better inform policy makers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in the context of refugee migration has mainly focused on one threat dimension covering symbolic, realistic, safety, and/or health concerns (e.g., Louis, Duck, Terry, Schuller, & Lalonde, 2007;Yitmen & Verkuyten, 2018), but only a few studies have explicitly distinguished between different threat types elicited by refugee migration (e.g., Abeywickrama, Laham, & Crone, 2018;Tartakovsky & Walsh, 2016). Furthermore, extensive refugee migration due to war and persecution can be accompanied by far-reaching changes in the receiving society.…”
mentioning
confidence: 99%
“…Noteworthy too, in the empirical articles, the reception of immigrants and refugees is examined in studies in a diverse range of contexts, focusing on Sicilian primary school teachers and a representative and large sample of U.S. voters (Espinosa et al., ), U.S. citizens, identified as White American (Mukherjee, Adams, & Molina, ), U.S.‐based White, Latino, and Asian samples (Huo, Dovidio, Jiménez, & Schildkraut, ), representative U.S., German, and Australian samples from the World Values Survey (Shin & Dovidio, ), Australian and U.S. citizens (Abeywickrama, Laham, & Crone, ), U.S. citizens (Marshall & Shapiro, ), and German residents who live close to a reception center for refugees and immigrants (Kotzur, Tropp, & Wagner, ). Adding to this breadth, these diverse samples are studied in five major immigrant and refugee receiving countries: Italy, the United States, Germany, Australia, and Switzerland (see Table ).…”
Section: The Current Issuementioning
confidence: 99%
“…Abeywickrama et al. () found in two studies among Australian and U.S. based samples that different migrant groups (economic migrants, refugees, asylum‐seekers) evoked different threats. Distinguishing in‐group morality threat from conflict‐based threat, they found that both types of threat predicted emotions and anti‐migrant bias.…”
Section: The Role Of Threat and Emotionsmentioning
confidence: 99%